Hypertriglyceridemia and hypertension-altered abdominal girdle phenotypes and their association with cardiovascular risk factors in women seen at the Provincial Climacteric Consultation - Elodia María Rivas Álpizar; Karen Lizeth García; Annia Quintana Marrero (Medisur)
Background: the presence of hypertension-increased abdominal circumference phenotypes is considered a cardiometabolic deterioration prognostic index. Objective: to determine the frequency of women with altered waist phenotypes and to establish the association between these and the main cardiovascular risk factors, as well as to estimate the global cardiovascular risk at 10 years. Methods: descriptive, correlational, cross-sectional study, which included 100 women who attended the Provincial Climacteric Consultation, at the Gustavo Aldereguía Lima Cienfuegos Hospital, from March 2016 to 2020. The analyzed variables were: age, skin color, smoking, arterial hypertension, obesity, physical activity, diabetes mellitus, body mass index, abdominal circumference, total cholesterol, uric acid, and triglycerides. The prevalence ratio was determined with a significance level of 95%. Results: the likelihood ratio showed a higher risk of presenting the phenotype in people over 45 years of age (1.47), obese (5.57), hypertensive (3.71) and diabetic (1.67). A significant association was found between smoking and physical activity with a probability ratio of 5.80 and 18, respectively. Conclusions: there is a significant relationship between altered abdominal waist phenotypes and the main cardiovascular risk factors, such as increased age, cardiovascular risk, diabetes mellitus, arterial hypertension, smoking, physical inactivity and obesity.